Moderation Of Trade Openness On The Effect Of Service Sector And Inflation On Indirect Tax Revenue - Harlan, Evan; Wijaya, Suparna (Educoretax, 2024)
This study aims to analyze the effect of service sector, inflation, and trade openness on indirect tax revenue in a number of countries in Latin America and the Caribbean. The results of this study are expected to provide additional insight into the knowledge of the factors that influence indirect tax revenue as well as the moderating effect of trade openness on the influence of the service sector and inflation in influencing indirect tax revenue in the region. This study uses secondary data on 15 countries with a period of 2009-2019. The analysis model used is multiple linear regression for panel data with panel-corrected standard errors. The results show that there is a significant effect of all independent and moderation variables on indirect tax revenue. Individually, the service sector has a negative effect on indirect tax revenue. However, after being moderated, the effect is weakened. Inflation also negatively affects indirect tax revenue, but this effect cannot be moderated by trade openness. Meanwhile, trade openness partially has a positive effect on indirect tax revenue. It is recommended that the government make policies that encourage trade openness because it has a positive impact on the economy, especially in the field of taxation.